Role of Glycated Albumin during Pregnancy - Suzanna Immanuel; Thoeng Ronald; Kanadi Sumapradja; Arini Setiawati3 (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the glycated albumin profile during pregnancy with normal glycemic status. Methods: We recruited 60 pregnant women between 21 and 36 weeks of gestation. We conducted several laboratory tests, such as glycated albumin, blood glucose, and albumin. These parameters were compared among four groups of gestational age (21-24 weeks, 25-28 weeks, 29-32 weeks, and 33-36 weeks) using ANOVA or Kruskal-Wallis test continued by Post-hoc test. Results: Glycated albumin was not statistically different among the groups. Albumin level of 33-36 weeks of gestation women (3.6 (SD 0.2) g/dl) was lower than 21-24 weeks of gestation women (3.8 (SD 0.2) g/dl). Conclusion: Glycated albumin level is not affected by gestational age. Therefore, glycated albumin may be used as glycemic status indicator during pregnancy from 21 to 36 weeks. [Indones J Obstet Gynecol 2017; 5-1: 16-18] Keywords: HbA1c, glycated albumin, glycemic status, pregnancy